CPEP: Centro de Pesquisa e Estudos Plinianos - Rossi, Andrea Lucia Dorini de Oliveira Carvalho [UNESP]; Vernaschi, Flávio Henrique Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Project is based on the creation of portal on the worldwide web, functioning as a Latin Sources database that will be both transcript and translate them to Portuguese. The sources on the database will be those related to Pliny the Younger and his interlocutors, namely: Pliny the Elder, Quintilian, Suetonius, Tacitus, Suetonius, Martial and Juvenal. The project aims at making transcriptions, translations and publishing the sources to portuguese as well as foment and publish the results of researches about these authors in the field of Classic Studies. The main objective of the project is to create a fomenting center of Latin Studies’ Researches about the Roman Principate (first and second centuries AD) produced by academic and scientific studies. Among the methodologies to be used, we shall focus on Discourse Analysis and theories concerning the epistolary gender and literary translation.

Em síntese o projeto é baseado na criação de um portal na worldwide web composto por um banco de dados de fontes latinas transcritas e traduzidas para o português. Essa base documental será composta com as fontes relacionadas a Plínio, o Jovem e seus interlocutores. Nesse rol constam Plínio, o Velho, Quintiliano, Suetônio, Tácito, Marcial e Juvenal. O projeto visa transcrever, traduzir e publicar as fontes para o português assim como incentivar e publicar resultados de pesquisas sobre esses autores tanto para pesquisadores de Estudos Clássicos. O principal objetivo do projeto é criar um centro fomentador de pesquisa em Estudos Latinos do Principado Romano nos seus dois primeiros séculos a partir do estudo acadêmico e científico. Dentre as metodologias do projeto, serão usadas a Análise do Discurso, assim como as teorias do gênero epistolar e da tradução literária.
Keywords: Pliny the younger; Research center; Database; Plínio o jovem; Centro de pesquisas; Banco de dados